Evaluasi Pener apan dan Pencapaian Standar Pelayanan Minimal pada Kab/Kota di Provinsi Kalim antan Timur - Gani, Irwan (FORUM EKONOMI, 2017)
The purpose of this research is to know the obstacles and problems faced by the Regency / City in East Kalimantan Province in the achievement and implementation of MSS. The focus of this research is the implementation and achievement of Minimum Service Standards (SPM) in East Kalimantan Province. Local government must have SPM in the implementation of public service including Balikpapan City Government. In the latest Regional Government Law, there are 6 (six) basic service areas which must have SPM namely education, health field, peace, public order and community protection, social affairs, public works and spatial arrangement and public housing field.Keywords: Minimum Service Standards